PENGARUH EFEKTIVITAS PENGGUNAAN, KEPERCAYAAN, KEAHLIAN PENGGUNA, DAN KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Maha Putra, I Kadek Agastia; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2016)
Currently the information system technology is growing rapidly, one of which is used for the betterment of the company. The technology used is an accounting information system (AIS). The company’s succes is determined by the employee performance. The purpose of this study is to determine the effectiveness of the use, confidence, user expertise, and the quality of accounting information system of employee performance. The population in this study were employees who use AIS in PT PLN (Persero) Distribution Bali. The samples obtained by saturation sampling technique as many as 71 respondents. Number of questionnaires distributed was 71 questionnaires, and questionnaires returned totaled 53 questionnaire. Analysis of the data used in this research is multiple regression analysis. The study found that the effectiveness of the use, confidence, user expertise, and the quality of accounting information systems positive influence on employee performance. It shows the four variables can improve employee performance.
Keywords: Usage Effectiveness, Trust, Expertise Users, Quality, Employee Performance